Volcanic history of Gölcük caldera (Isparta, Türkiye) with evidence for a Holocene explosive eruption - Atıcı, Gokhan; Friedrichs, Bjarne; Çobankaya, Mehmet; Danišík, Martin; Atakay, Evren; Yurteri, Esra; Schmitt, Axel Karl (Journal of volcanology and geothermal research, 2025)
Modern Lake Gölcük near the city of Isparta partially fills a caldera that is the focal point of protracted alkaline, potassic-ultrapotassic volcanism in southwestern Anatolia. Because of Gölcük's proximity to a major regional urban center, and field indications for far-reaching pyroclastic density currents (PDC) erupted from this caldera, improved constraints on eruptive recurrence and timing are required. Through field work and combined UTh and (UTh)/He zircon geochronology, the duration of known volcanism at Gölcük has been extended, both to older and, importantly, to younger ages than previously reported. Early activity in the Late Miocene-Pliocene (Stage 1, 6.0-4.2 Ma) was mostly effusive, whereas explosive activity started in the Early Pleistocene (Stage 2, 2.2-1.8 Ma) forming nine PDCs of the Serençay valley ignimbrite sequence. Following a hiatus, PDC and fallout emplacement resumed during Stage 3 (520-480 ka) and Stage 4 (150 ka), with the modern caldera likely being the result of the Stage 4 Çay ignimbrite eruption. UTh zircon crystallization ages of antecrysts, especially in Stage 4 and 5 pumice, clearly implicate Gölcük as the source of the Stage 2 and 3 explosive eruptions. Stage 5 includes effusive activity and dome formation, but also at least four explosive eruptions starting at c. 24 ka. The discovery of the here termed Isparta ignimbrite, which erupted from Gölcük caldera at 10.7 ± 0.7 ka (2 σ uncertainty), identifies it as an active volcano. Frequent eruptions at recurrence intervals of 4-5 ka during the Late Pleistocene-Holocene transition warrant future research regarding its hazard potential. This also implies that Gölcük may have erupted distal tephra markers for this climatically important interval.